Exploring Green Business Practices in Indonesian SMEs: A Descriptive Qualitative Study - Zulfa Rojauna Syafriani (Generate Digital Publishing, 2025)
Objectives: This study aims to examine in depth the application of green business practices in small and medium enterprises (SMEs) in Indonesia, focusing on the level of understanding, motivation, challenges, and impacts resulting from the implementation of sustainable practices in the local economic context. Research Design & Methods: Using a descriptive qualitative approach, data were collected through in-depth interviews with 12 SMEs actors representing various sectors, including food and beverages, fashion, crafts, and creative services. Thematic analysis was conducted to identify patterns related to motivation, practices, barriers, and outcomes. Findings: The study concludes that green business implementation among Indonesian SMEs is diverse, shaped by both internal and external motivations. Despite facing structural, technical, and financial challenges, applying sustainability principles yields notable economic, social, and environmental benefits. This makes green business an effective strategy to enhance competitiveness and support sustainable development. Implications & Recommendations: This study recommends the importance of strengthening the supporting ecosystem through cross-sector collaboration between the government, financial institutions, academics, and industry players. Policy interventions oriented towards green incentives, technical assistance, and ease of access to financing will accelerate the transition of SMEs towards sustainable business practices. Contribution & Value Added: This study provides empirical contributions to the literature on SMEs transformation in the context of the green economy in developing countries, particularly Indonesia. In addition, the results enrich the understanding of SMEs adaptive strategies in facing resource constraints while innovating towards environmental and social sustainability.